High force catch bond mechanism of bacterial adhesion in the human gut - Zhaowei Liu (Nature Portfolio, 2020)
Understanding bacterial adhesion is important in a number of different areas of study. Here using a range of simulations and experimental methods, the authors, report on the molecular mechanism behind the binding of bacteria to cellulose fibers at high shear force in the human gut.